Temporal and spatial variability of traffic-related PM2.5 sources: Comparison of exhaust and non-exhaust emissions. (1st February 2019) - Jeong, Cheol-Heon; Wang, Jon M.; Hilker, Nathan; Debosz, Jerzy; Sofowote, Uwayemi; Su, Yushan; Noble, Michael; Healy, Robert M.; Munoz, Tony; Dabek-Zlotorzynska, Ewa; Celo, Valbona; White, Luc; et al.
Abstract: The contribution of traffic-related particulate matter (PM2.5, particles smaller than 2.5 μm in diameter) sources can vary temporally and spatially, which may disproportionately contribute to health outcomes. Furthermore, non-exhaust emissions are a growing concern due to the high concentrations of redox active metals that can be present. The temporal and spatial variabilities of traffic-related PM2.5 sources were investigated in this study by comparing source contributions between two near-road sites. In order to identify local PM2.5 sources with greater temporal and spatial resolution, receptor modeling was performed for hourly-resolved organics, inorganic ions, trace elements, and black carbon in PM2.5 simultaneously measured at downtown and highway sites located within 15 m of a major roadway and highway, respectively, in Toronto. The source apportionment study revealed that traffic-related PM2.5 sources were mainly from exhaust emissions (9%–19% of PM2.5 ) and non-exhaust emissions including brake wear (2%–6%) and resuspension of road dust (3%–4%). The traffic-related sources exhibited strong diurnal and spatial variabilities, whereas no spatial and temporal differences were observed for the largest PM2.5 contributors, oxidized organic aerosol and secondary sulphate. During morning rush hours, the overall contribution of traffic exhaust and non-exhaust emissions were elevated up to 35%–48% of total PM2.5 mass, which was found to be the largest PM2.5 source at the highway site and the second largest contributor in the downtown area. Furthermore, the contribution of traffic-related sources at the highway site was higher than at the downtown site by a factor of 2–3, suggesting that exposure to traffic-related emissions varies greatly in space and time. Nearly one-third of the traffic-related source contributions were associated with non-exhaust emissions from brake wear and road dust resuspension in the urban environment. Elevated levels of non-exhaust sources were correlated with the number of heavy-duty vehicles, rather than total traffic volume. Although the contribution of brake wear and road dust sources to total PM2.5 mass was relatively low, non-exhaust emissions contributed a substantial fraction of trace elements, especially for Ba (74–79%), Cu (66–71%), and Mn (53–65%) in the urban atmosphere. Highlights: Hourly chemical speciation in downtown and highway revealed traffic-related PM2.5 . Exhaust/non-exhaust emissions accounted for half of PM2.5 during morning rush hours. Non-exhaust emissions were mainly from brake wear and resuspension of road dust. Non-exhaust emissions contributed a substantial fraction of potentially toxic trace metals.